Sosialisasi dan Edukasi Pengelolahan Piutang Sebagai Upaya Meningkatkan Profitabilitas Pada Rumah Sakit Pusri Palembang - Putri, Seranti; Mellita, Dina; F, Fitriasuri; Elpanso, Efan; Noviardy, Andrian; H, Heriyanto (Yayasan Daarul Huda Kruengmane, 2025)
To maintain financial stability and increase hospital profitability, accounts receivable management is essential. The purpose of this study was to assess the various approaches used to manage accounts receivable at Pusri Hospital, make policy recommendations, and increase hospital staff awareness and understanding through socialization and education. This study used a descriptive quantitative approach by analyzing financial data and conducting in-depth interviews with the head of the hospital's finance department. To determine how effective accounts receivable management is, activity and profitability ratio analysis was conducted. A conference with the head of the finance room was conducted to obtain information on current policies and practices, as well as to provide suggestions based on the results of the study. The results showed that the accounts receivable turnover of Pusri Hospital has fluctuated over the past three years. In 2022, accounts receivable turnover decreased drastically as a result of ineffective claims management. The results of the interviews showed that the hospital recognized the need for policy improvements, including the implementation of an ERP system to help manage accounts receivable in a more integrated and effective manner. This study led the hospital to commit to improving the accounts receivable management process, including socializing payment policies to patients. This study includes independent study findings that include strategic analysis and advice. They are expected to help Pusri Hospital increase profitability and maintain stable cash flow in the future.